Analisis Pelaksanaan Retensi dan Pemusnahan Berkas Rekam Medis di Rumkital dr Ramelan Surabaya - Eltigeka Devi Apriliani; Indah Muflihatin; Niyalatul Muna (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2020)
The first time retention at RUMKITAL Dr. Ramelan Surabaya were conducted in 2008. Based on data patient visits of Dr. RUMKITAL Ramelan Surabaya from 2015 to 2019 had increased it caused the storage shelf could not accommodate medical record files. SPO (Standard Procedure Operational) about implementation of retention and destruction of medical records in Dr. RUMKITAL Ramelan Surabaya not found provisions of the storage inaktif medical record file. The aim of this research was to analyze the implementation of retention and destruction medical record files in Dr. Ramelan Surabaya with identifying using 5M (Man, Money, Material, Machine, Method) and the USG method (Urgency, Seriousness, Growth) to determine the priority of problem. This research is qualitative research and collecting the data using observations, interview, and documentation. The subject of study is 1 scan officer of medical record and 2 officer of medical record. The results of this research is got 3 priority cause of problem the implementation of retention and destruction of medical record are elements of method, material and machine. The suggestion of this problem are improving the SPO (Standard Procedure Operational) and implementation the system information of retention.